Falsidade ideológica em compras com cartão não presente e comparação entre modelos de prevenção - Freitas, Marcos Aurélio de (2013)
In purchases conducted over the internet or by telephone, in many countries like Brazil and USA, credit cards are not presented during the sales process and authentication mechanisms (such as passwords) are not popular among consumers. At the same time, the merchants are held liabe for fraudulent transactions. In every study before this one, credit card fraud detection was not focused only on these channels nor on the key stakeholders of this process, the merchants. This work shows the results of using five popular techniques in the literature for credit card fraud detection and also analyzes the power of sharing databases by comparing the techniques when applied either on a single store database or on a shared database which includes data from many stores.